Knowledge, attitudes and nutritional practices of health sciences students - Mucha Hospinal, Luis Florencio (2020)
Objective. To characterize and compare the knowledge, attitudes and nutritional practices of students of Dentistry, Psychology and Obstetrics at the Universidad Peruana Los Andes de Huancayo. Methods. Basic type of research and non-experimental, cross-sectional, descriptive comparative design. The sample which was non-probability and intentional, was composed of 35 Dentistry, 35 Psychology and 35 Obstetrics students. It was applied the “questionnaire on knowledge, attitudes and nutritional practices of university students”, validated by the judgment of three experts in human nutrition. Results. It was found that 66.6 % of the students consumed three meals a day, 52% had breakfast inter-daily and 45 % daily; 86.7 % consumed food in the kiosks adjacent to the campus and 48.6% had breakfast during school hours. Knowledge of the function of dairy products was 96 %, meat 76.3%, sausages and hamburgers 49.7 %, fruits 78.3 %, edible vegetables 91 %, soft drinks 38.7 % and sweets 63.7 %. Conclusions. According to the necessary nutritional competences in students of Health Sciences, there are deficiencies in the knowledge, attitudes and nutritional practices of the studied population; with relevant percentage differences among the three careers.